Cyber Security in the Nigerian Banking Sector: An Appraisal of Audit Committee Effectiveness - Ojeka, Stephen A.; Ben-Caleb, Egbide; Ekpe, Edara-Obong Inyang (International Review of Management and Marketing, 2017)
This study appraises the relationship that exists between cyber security and audit committee effectiveness using audit committee independence, audit committee technological expertise and audit committee financial expertise characteristics as independent variables. The variable used to measure the dependent variable is cyber security compliance. Thirteen (13) banks listed on the Nigerian Stock Exchange were selected. Empirical Analysis was carried out using product moment correlation and ordinary least square regression analysis methods. The result showed that audit committee characteristics as measure by independence, financial expertise and technological expertise all have non-significant negative relationship to cyber security in the Nigerian Banking sector. The implication is that, the audit committee as presently constituted in Nigeria would be unable to provide controls and oversight functions over cyber security in the banking sector which is the most sensitive sector in the economy. It was therefore recommended that the composition of the audit committee in Nigeria should be worked on to deliberately incorporate needed technological and financial experts that can ask probing questions and offer their wealth of experience in safeguarding the shareholders wealth and lastly, the committee members should be seen to be independent. Keywords: Audit Committee, Banking sector, Cyber security, Financial Expertise, Independence and Nigeria JEL Classification: M4